The modern methods of reproduction physiology of horses - A. V. Tkachev; O. L. Tkacheva; B. V. Gutyj (Ukrainian Journal of Veterinary and Agricultural Sciences, 2019)
The concept of development of horse breeding in Ukraine until 2020 provides for an increase in the number of horses through the intensive use of modern methods of reproduction biotechnology. However, the imperfection of these methods hinders their widespread use in practice. The aim of the work was to draw attention to the most important problems of the physiology of horse reproduction in Ukraine and to show ways to solve them that have already been proposed by domestic and foreign researchers. The development strategy of the physiology of horse reproduction in order to increase its effectiveness should take into account the least studied aspects that were discussed above. The article shows that taking into account the influence of micromycetes, the absolute number of colony forming units of E. coli in semen of stallions; immuno-and cytogenetic features; new methods of sanitary preparation of horses for sperm and insemination; the effect of permissible levels of feed mycotoxins on physiological functions improves the efficiency of equine reproduction physiology methods. However, we first discovered new physiological features of the effect of erythrocyte antigens of blood groups of horses of Ukrainian selection on the indicators of their native sperm. In the presence of ad/bcm and dg/cgm alleles of the blood group D system in stallions, sperm motility is on average less than 5 points; alleles ad/cgm, ad/d, ad/de, ad/dk, bcm/d, bcm/de, bcm/dg, bcm/dk, cegm/cgm, cegm/d, cegm/dg, cegm/dk, cgm/ceg, cgm/cgm, cgm/dg, cgm/dk, de/cgm, de/dk, dg/di, dk/d, dk/de, dk/dk is accompanied by sperm motility from 5 to 7 points; alleles bcm/cgm, dg/dk, de/d, cgm/d, cgm/de sperm motility is observed more than 7 points. The results obtained allowed us to develop for practice ways to increase the efficiency of sperm cryopreservation by immunogenetic parameters. In addition, open physiological correlations can increase the fertility of mares during mating.